PENINGKATAN KREATIVITAS KERJA GURU DENGAN MEMPERBAIKI BUDAYA ORGANISASI DAN EFIKASI DIRI - Fenni Sartana; Muhamad Entang; Yuyun Elizabeth Patras; Sutji Harijanto (JURNAL MANAJEMEN PENDIDIKAN, 2020)
IMPROVING THE TEACHER CREATIVITY BY IMPROVING THE ORGANIZATION AND SELF-EFICATION CULTUREThe purpose of this reseach is to determine the correlation between organization culture and self efficacy toward teacher’s creativity. This study is conducted in Vocational High School at Region of Cibinong. The study population is 283 teachers and the number of sample is 166 teachers decided by proportional random sampling. Data was collected by questionnaire. The data analysis technique used correlation regression partial and multiple. The result shows that there is positive correlation between organization culture and teacher’s creativity (the correlation coefficient ry1 = 0,661 and the detemination coefficient r2y1=0,437), there is positive correlation between self efficacy and teacher’s creativity (the correlation coefficient ry2 =0,609 and the determination coefficient r2y2=0,370), and there is positive correlation  of organization culture and self efficacy to teacher’s creativity (the correlation coefficient ry12 = 0,716 and the determination coefficient r2y12= 0,513). Based on the result, it can be concluded that the teacher’s creativity could be enhanced through organization culture and self-efficacy either partially or concurrently